Facile synthesis of Tb-decorated graphene oxide: electrochemical stability, hydrogen storage, and corrosion inhibition of Mg AZ13 alloy in 3.5% NaCl medium. Issue 2 (24th December 2020) - Nagarajan, Palaniappan; Cole, Ivan S.; Kuznetsov, Aleksey; Manickam, Sivakumar
Abstract : Terbium functionalized graphene oxide interacted with an Mg 2+ surface by the active side of GO. Abstract : Magnesium alloys have been broadly used due to their lightweight and high ductility. However, they are subject to corrosion which deteriorates their properties. To develop a novel corrosion inhibitor coating for Mg alloys, we performed functionalization of a graphene oxide (GO) matrix with Tb(iii ) to improve the electrochemical behaviour and coating stability of a GO and Tb composite on the metal alloys in corrosive medium. The functionalized terbium GO material was characterized by microscopy, spectroscopy, and XRD techniques to confirm the non-covalent interactions on the active surface of the host material. The corrosion inhibition was found to be ca. 80% and electrochemical stability was observed to be high at a voltage of 900 mV. Computational studies also support the potential anti-corrosion applications of this material.